Yours, Mine and Ours: Theorizing the Global Articulation of Qualitative Research Methods and Academic Disciplines - Bryan C. Taylor (Romanian Journal of Communications and Public Relations, 2016)
Two current forms of globalization are inherently interesting to academic qualitative researchers. The first is the globalization of qualitative research methods themselves. The second is the globalization of academic disciplines in which those methods are institutionalized as a valuable resource for professional practices of teaching and scholarly research. This essay argues that patterns in existing discussion of these two trends create an opportunity for innovative scholarship. That opportunity involves reflexively leveraging qualitative research methods to study the simultaneous negotiation by academic communities of both qualitative methods and their professional discipline. Five theories that serve to develop this opportunity are reviewed, focusing on their related benefits and limitations, and the specific research questions they yield. The essay concludes by synthesizing distinctive commitments of this proposed research program.